2008
DOI: 10.1113/jphysiol.2008.153734
|View full text |Cite
|
Sign up to set email alerts
|

Initial segment Kv2.2 channels mediate a slow delayed rectifier and maintain high frequency action potential firing in medial nucleus of the trapezoid body neurons

Abstract: The medial nucleus of the trapezoid body (MNTB) is specialized for high frequency firing by expression of Kv3 channels, which minimize action potential (AP) duration, and Kv1 channels, which suppress multiple AP firing, during each calyceal giant EPSC. However, the outward K + current in MNTB neurons is dominated by another unidentified delayed rectifier. It has slow kinetics and a peak conductance of ∼37 nS; it is half-activated at −9.2 ± 2.1 mV and half-inactivated at −35.9 ± 1.5 mV. It is blocked by several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
163
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(184 citation statements)
references
References 52 publications
20
163
0
1
Order By: Relevance
“…Such inactivation of potassium currents is consistent with the substantially broader spikes evoked from Ϫ70 mV (1.02 Ϯ 0.06 ms) compared with spikes evoked from Ϫ80 mV (0.83 Ϯ 0.04 ms, n ϭ 7; p ϭ 0.04). This effect is consistent with previous evidence for a major role of I A in repolarization of action potentials in CA1 pyramidal neurons (Kim et al, 2005;Andrásfalvy et al, 2008) and it is also possible that steady-state inactivation of other channel types such as Kv1 family (D-type) or Kv3 family channels could be involved. These results show that the relative role of Kv2 channels in early action potential repolarization in CA1 pyramidal neurons depends on resting potential, with a significant role in early repolarization for action potentials elicited from Ϫ70 mV.…”
Section: Effect Of Gxtx-1e On Action Potential Shape In Hippocampal Csupporting
confidence: 80%
See 3 more Smart Citations
“…Such inactivation of potassium currents is consistent with the substantially broader spikes evoked from Ϫ70 mV (1.02 Ϯ 0.06 ms) compared with spikes evoked from Ϫ80 mV (0.83 Ϯ 0.04 ms, n ϭ 7; p ϭ 0.04). This effect is consistent with previous evidence for a major role of I A in repolarization of action potentials in CA1 pyramidal neurons (Kim et al, 2005;Andrásfalvy et al, 2008) and it is also possible that steady-state inactivation of other channel types such as Kv1 family (D-type) or Kv3 family channels could be involved. These results show that the relative role of Kv2 channels in early action potential repolarization in CA1 pyramidal neurons depends on resting potential, with a significant role in early repolarization for action potentials elicited from Ϫ70 mV.…”
Section: Effect Of Gxtx-1e On Action Potential Shape In Hippocampal Csupporting
confidence: 80%
“…We believe the GxTX-resistant current likely contains multiple components, because the speed and degree of inactivation varied considerably from cell to cell. Based on previous analysis of potassium currents in hippocampal and cortical pyramidal neurons, the GxTXresistant current includes components from Kv4 and Kv1 family subunits (Kim et al, 2005;Chen et al, 2006;Guan et al, 2007aGuan et al, , 2007bGuan et al, , 2011Carrasquillo et al, 2012;Kim and Hoffman, 2012). We found that some of the GxTX-resistant current could be blocked by 1 mM TEA, but this block was not selective because 1 mM TEA also clearly partially inhibited the slowly-activating slowly-deactivating GxTX-sensitive component of current.…”
Section: Gxtx-1e Inhibits Most Delayed-rectifier Potassium Current Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas K V 3 channels turn on and off with the rising and falling phases of the action potential, the slower K V 2 channels may hyperpolarize the interspike potential and thereby expedite recovery of Na V channels from inactivation. Such a mechanism was suggested for MNTB neurons, in which K V 2.2 channels were enriched on one part of the AIS (Johnston et al, 2008). The role of K V 2.2 channels awaits investigation in ANFs, in which they are positioned along internodes (Fig.…”
Section: K V Channels Of Distinct Class and Topography In Anfsmentioning
confidence: 99%